Effects of feeding fermented sago pith meal on the growth performance of broiler chickens - Ab. Jalil, Azilah; Abdullah, Norhani; Alimon, Abdul Razak; Abd Aziz, Suraini (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
Rhizopus sp. was used to improve the nutritive value of sago pith meal by solid state fermentation (SSF). The optimized conditions for SSF were moisture 50ml/50 g substrate, pH 6.0, 30°C and 1% ammonium sulphate for 44h incubation. The crude protein increased but the crude fibre decreased slightly. Feeding broiler chickens with diet containing fermented SPM (Diet C) increased the average weight gain to 1.33±0.143 kg but group fed on diet containing untreated SPM (Diet B) had lower weight gain 1.27±0.162 kg. The FCR of Diet C group was higher than FCR of Diet A group; 2.15±0.243 and 1.99±0.316, respectively. The organs to live weight ratios of liver, bursa, heart, spleen and gizzard were not significantly different and the hepatic histopathology did not show any abnormalities. Fungal fermentation enhanced the nutritive value of SPM and broilers fed diet containing 25% of fermented SPM during the grower-finisher period showed better feed efficiency when compared to broilers fed untreated SPM.